A forward model for the helium plume effect and the interpretation of helium charge exchange measurements at ASDEX Upgrade. (23rd March 2018) - Kappatou, A; McDermott, R M; Pütterich, T; Dux, R; Geiger, B; Jaspers, R J E; Donné, A J H; Viezzer, E; Cavedon, M
Abstract: The analysis of the charge exchange measurements of helium is hindered by an additional emission contributing to the spectra, the helium 'plume' emission (Fonck et al 1984 Phys. Rev. A29 3288), which complicates the interpretation of the measurements. The plume emission is indistinguishable from the active charge exchange signal when standard analysis of the spectra is applied and its intensity is of comparable magnitude for ASDEX Upgrade conditions, leading to a significant overestimation of the He 2+ densities if not properly treated. Furthermore, the spectral line shape of the plume emission is non-Gaussian and leads to wrong ion temperature and flow measurements when not taken into account. A kinetic model for the helium plume emission has been developed for ASDEX Upgrade. The model is benchmarked against experimental measurements and is shown to capture the underlying physics mechanisms of the plume effect, as it can reproduce the experimental spectra and provides consistent values for the ion temperature, plasma rotation, and He 2+ density.